Differential Mechanisms Drive Species Loss Under Artificial Shade and Fertilization in the Alpine Meadow of the Tibetan Plateau - Li, Junyong; Charles, Lachlan S.; Yang, Zhongling; Du, Guozhen; Fu, Shenglei (Frontiers in Plant Science, 2022)
Fertilization is an effective management strategy to promote community biomass but can simultaneously reduce species diversity in many grassland systems. Shifts in competition for resources have been proposed to explain the decline in plant species diversity due to fertilization, yet the underlying mechanism driving species loss remains controversial. This uncertainty may be driven by variation in above and belowground resource availability. However, experiments simultaneously manipulating both light availability and soil nutrients are rare. Using a six years field experiment to manipulate light availability (via shade cloth) and soil nutrients (via fertilizer addition), we tested this resources competition hypothesis in a species-rich alpine meadow by examining variation of species traits associated with capacity of light acquisition within these treatments. Our results showed that artificial shade decreased community biomass accumulation whereas fertilization increased it. In constrast, both shade and fertilization reduced species diversity. Extinction of non-Gramineae species (e.g. Fabaceae and Cyperaceae) was the main reason of species diversity decline. Species loss can be explained by the limitation of light availability and predicted by species traits associated with light acquisition capability under fertilization and low light tolerance under artificial shade. Specifically, fertilization eliminated species with lower stature and artificial shade exterminated species with higher light compensation point. The findings suggest that light availability is consistently important for plant growth and that low competitiveness for light under fertilization and intolerance of low light conditions under artificial shade trigger species loss process in the alpine meadow.Our experiment help clarify the mechanisms of how artificial shade and fertilization decreased species diversity, and highlight that light compensation point, which tends to be neglected by most of studies, is one of the vital drivers in determining species coexistence.